Pengaruh Insentif Pegawai dan Motivasi Kerja Terhadap Kinerja Pegawai di Satuan Kerja Lalu Lintas Polresta Samarinda - Yuniar, Renita; Jubaidi, Jubaidi; Efendi, Achmad (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the effect of employee incentives and work motivation on employee performance at the Samarinda Police Traffic Work Unit. This study uses a quantitative approach with a survey method and distributes questionnaires to 92 respondents selected through a total sampling technique from a population of 120 employees. The data were analyzed using multiple linear regression using SPSS version 27. The results of the study indicate that employee incentives and work motivation each have a partial positive and significant effect on employee performance. Simultaneously, both also show a significant effect on employee performance with a coefficient of determination (R²) of 0.790, which means that 79% of employee performance variables can be explained by incentives and work motivation. This study concludes that increasing incentives and work motivation contributes significantly to improving employee performance, and suggests the importance of improving the incentive system and strengthening the motivational aspect in human resource management in the police environment.